Muslim Cosmopolitanism: Recovering a Forgotten Stream in the history of Islam (American Journal of Islam and Society, 2014)
On November 8, 2013, Syed Muhd Khairudin Aljunied (National Universityof Singapore; Fulbright Fellow, Columbia University) addressed the topic of“Muslim Cosmopolitanism.” The event was held at the IIIT headquarters inHerndon, Virginia.He began his talk with a personal example: He is the child of an Arab fatherand an Indian mother, his culture is Malay, he prefers to talk in eitherMalay or English, and he understands Chinese. Thus, he is a living exampleof his assertion that “being Muslim is part and parcel of being able to appreciate many cultures … We are all hybrids,” and therefore it is only natural forMuslims to embrace diversity. While this was true for the first millennium ofIslamic civilization, it is, unfortunately, “not the case today.”Aljunied cited several examples of how contemporary Muslims have putthis reality aside. For example, he raised the question of why, when a Muslimengages in something that is clearly wrong, do Muslims apologize by sayingthat he/she is a “bad Muslim,” instead of a “bad person,” or become offensiveby saying that the action was somehow justified. He noted that this is “an unhealthydevelopment in the world in general, and especially in the UnitedStates” – one that Muslims should abandon. Instead, Muslims need to studytheir history and understand exactly who they are. With this goal in mind, hepraised AbdulHamid AbuSulayman’s Crisis in the Muslim Mind (IIIT: 1993)for its analysis of such concerns ...